The Significance of Doorway Positions in English Medieval Parochial Churches and Chapels - Sedlezky, Geoffrey (Archaeopress, 2023)
This book analyses the positions of external church doorways in England to investigate the significance that positioning had for the function and design of these buildings. The author proposes a link between the design and function of parochial churches and chapels with the number and attributes of their doorways.